Verbal and Visual Sign in “Encanto” Movie Posters - Karenski, I Wayan Jason; Puspani, Ida Ayu Made; Mulyawan, I Wayan (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2023)
This research deals with the movie poster of “Encanto” as the object of the study under semiotic theory. The aim of this research is to identify the semiotic signs that are contained in “Encanto” movie posters and to analyse the meaning of signs that are accomplished in “Encanto” movie posters. The data of this research is 6 movie posters of “Encanto”. This research employed a convenience sampling method to answer the research question. The data was taken from the Internet Movie Poster Awards on http://www.impawards.com. The data was analyzed based on the theory according to Dyer's concept of verbal and visual indicators (1982). Second, the meanings of the signs were analyzed according to the theory of signifiers and signified by Saussure (cited in Chandler, 2007) and supported with the colour term by Olesen (2013). There were nine verbal signs in those movie posters. The visual signs in those movie posters such as appearance, manner, otivity, background, and the colour. The application of color meaning by using the color terms of Olesen.